Lactobacillus plantarum L5 production: a statistical approach / Nurul Ashikin Mat - Mat, Nurul Ashikin (2015)
The survival characteristic of Lactobacillus plantarum in the harsh environment of human gastrointestinal (GI) tract has been manipulated to make it as one of the safest probiotic to be commercialized. According to the market report, the global probiotic products market was estimated at USD 58,700.3 million in 2013 and is expected to reach USD 96,046.8 million by 2020 due to unexpected success in health benefit and extreme competition from developers and suppliers (Chaudhari, 2015). However, the production of probiotics in large-scale using traditional method requires high cost, high energy and time consuming. So, the implementation of design of experiment (DoE) in the bioprocess of L. plantarum to speed up and increase its productivity is significantly necessary. The objective of this research is to identify the main and interaction effects of two variables (temperature, and agitation speed) on bio-mass production of L. plantarum L5 strain. The experiment was designed using 22 factorial methods and was duplicated twice. The main effect of incubation agitation speed on L. plantarum L5 not significant (F(l,4) =0.141,p =0.727), but the main effect of temperature on L. plantarum L5 growth was significant such that cultivation of L. plantarum L5 at high speed produced maximal OD than cultivation of L. plantarum L5 at low speed (F(l,4) = 15.08, p = 0.018). There were significant interaction effects between temperature and agitation speed, p<0.05 on maximum OD and specific growth rate. Results obtained from present study indicate that there is interaction effect of temperature and agitation speed on the maximum optical density (OD) and specific growth rate of L5. Implementation of design of experiment (DoE) has potential alternative method to estimate the effects of variables on the productivity of Lactobacillus plantarum L5.